Animals in War in Historical Mesopotamia - Battini, Laura (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2019)
Mesopotamian official art is full of war and hunting images from the last IV mill. BC. onwards. This paper focuses on animals used in human wars and on relationships between animals and men. By using images and texts it is possible to reach a better understanding of this forgotten topic.